Sorption of strontium on the composite sorbent based on cellulose and hydrated antimony pentoxide - V. V. Galysh; M. T. Kartel; W. Janusz; E. Skwarek; A. A. Nikolaichuk (Хімія, фізика та технологія поверхні, 2017)
In this study cellulose-inorganic sorbents based on bleached cotton fibres and hydrated antimony pentoxide were prepared and used for strontium ions sorption from model aqueous solutions. The adsorption of strontium ions was determined by the radiotracer method using radioisotopes. A comparative analysis was made of sorption properties of the obtained sorption materials with different contents of hydrated antimony pentoxide towards strontium ions. The efficiency of strontium sorption increases with the increase in the modifier content in the composite cellulose-inorganic sorbents. The maximum efficiency of strontium sorption from solution (99 %) and the maximum distribution coefficient (1400 ml/g) correspond to the sorbents with the hydrated antimony pentoxide content 2.9 %. The effect of pH on the density of ions sorption on the cellulose-inorganic sorbent and the distribution coefficient was investigated. The experimentally determined density of ions sorption and distribution coefficient for strontium varied between 0.045 and 0.076 µmol/m2 and between 100 and 1400 ml/g respectively depending on pH of model aqueous solutions. Chemical and structural properties were investigated by the low temperature nitrogen adsorption–desorption method, X-ray diffraction, infrared spectroscopy, differential thermal analysis. Surface area of the sorbents was determined by Brunauer, Emmett and Teller method. All composite cellulose-inorganic sorbents were characterized by a low specific surface area (1 m2/g). Hydrated antimony pentoxide characterized by amorphous structure and modification process does not affect cellulose crystallinity.